Bacterial communities in aquaponic systems: Insights from red onion hydroponics and koi biological filters - Bambang Widyo Prastowo; Indarti Puji Lestari; Ni Wayan Sri Agustini; Dody Priadi; Yati Haryati; Akhmad Jufri; Puspita Deswina; Eko Binnaryo Mei Adi; Iskandar Zulkarnaen (Case Studies in Chemical and Environmental Engineering)
Aquaponics is a sustainable food production technology combining the tripartite relationship between fish, plants, and microorganisms. This study discusses the diversity and characteristics of bacteria communities in different aquaponic system compartments. Samples from red onion hydroponic compartment and koi biological filters were collected and analyzed for their bacterial community structure. Gene sequencing with high throughput 16S rRNA is used to analyze bacterial communities. Hydroponic compartments had significantly more bacterial communities than koi biological filters. The most dominant phylum in the hydroponic compartment is Proteobacteria (α, β, γ), Bacteroidota, Firmicutes, Planctomycetota, Cyanobacteria, and Actinobacteria. While in the biological filter are Bacteroidota, β-Proteobacteria, and Actinobacteria. The bacterial community in the hydroponic compartment showed significant specificity compared to the bacterial community in the biological filter. We also systematically describe bacterial communities in hydroponic compartments and biological filters and estimate their relevant functions in biological filtration of water. These results provide new insights into bacterial communities’ role in the hydroponic compartment for red onion growth as well as bacterial communities in the biofilter that act as bioremediation agents on water quality that affect the growth and survival of koi. However, it would be required a deeper analysis to identify its specific roles in aquaponics.